Fundamental Technologies and Recent Advances of Cell-Sheet-Based Tissue Engineering - Imashiro, Chikahiro (Int J Mol Sci, 2021)
Tissue engineering has attracted significant attention since the 1980s, and the applications of tissue engineering have been expanding. To produce a cell-dense tissue, cell sheet technology has been studied as a promising strategy. Fundamental techniques involving tissue engineering are mainly introduced in this review. First, the technologies to fabricate a cell sheet were reviewed. Although temperature-responsive polymer-based technique was a trigger to establish and spread cell sheet technology, other methodologies for cell sheet fabrication have also been reported. Second, the methods to improve the function of the cell sheet were investigated. Adding electrical and mechanical stimulation on muscle-type cells, building 3D structures, and co-culturing with other cell species can be possible strategies for imitating the physiological situation under in vitro conditions, resulting in improved functions. Finally, culture methods to promote vasculogenesis in the layered cell sheets were introduced with in vivo, ex vivo, and in vitro bioreactors. We believe the present review that shows and compares the fundamental technologies and recent advances for cell-sheet-based tissue engineering should promote further development of tissue engineering. The development of cell sheet technology should promote many bioengineering applications.